Bank Efficiency and Openness in Africa: Do Income Levels Matter? - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2010)
This paper integrates a previously missing wealth-effect component in the openness-finance debate. From a panel of 29 low and middle income African countries with data spanning from 1987 to 2008, we provide evidence that openness (trade and financial) triggers less bank efficiency in low income countries than in their middle income counterparts. These findings justify the absence of a banking comparative advantage and consequently, the issue of over-liquidity resulting from low funding of economic operators with mobilized financial deposits. In terms of policy implications, globalization increases economic cost of banks in sampled countries, with trade openness more detrimental than financial openness. Banks in middle income countries play a greater role in financing activities resulting from trade openness than those in low income countries. Also, a lot needs to be done on the improvement of infrastructures that curtails information asymmetry in the banking industry.
Keywords: F10; G20; I30; 330; Banking; Intermediation Efficiency; Openness; Panel Data; Africa